2014
DOI: 10.1080/13614568.2014.983557
|View full text |Cite
|
Sign up to set email alerts
|

A community for grieving: affordances of social media for support of bereaved parents

Abstract: The purpose of this paper was to study bereaved parents' use of a closed peer grief support community on Facebook and the features of the community that are important to them. The death of a child is an uncomfortable subject in most contemporary societies. This limits the exploration of experiences and possibilities for coping with grief. However, with the introduction of social media, this has changed. Theoretical perspectives on parental grief recognizing the importance of continued relational bonds with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…As the findings demonstrate, the Facebook group provided members with the ability to connect with a large network in the host country, facilitating their access to diverse and suitable information and support resources. Due to the large audience and the real-time interaction available through the group, there were always many people available and likely to respond quickly to requests for information (see also Hård af Segerstad and Kasperowski, 2015). The large number of group members increased the information-seeker's possibilities of finding relevant information in the group.…”
Section: The Activities Through An Affordance Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…As the findings demonstrate, the Facebook group provided members with the ability to connect with a large network in the host country, facilitating their access to diverse and suitable information and support resources. Due to the large audience and the real-time interaction available through the group, there were always many people available and likely to respond quickly to requests for information (see also Hård af Segerstad and Kasperowski, 2015). The large number of group members increased the information-seeker's possibilities of finding relevant information in the group.…”
Section: The Activities Through An Affordance Perspectivementioning
confidence: 99%
“…Indeed, research now shows that many user groups (for example, grieving parents, stay-at-home fathers, immigrants and patients) join Facebook groups to meet others, discuss information of mutual interest, support one another, and overcome societal stigmas and taboos (for example, Ammari and Schoenebeck, 2016; Hård af Segerstad and Kasperowski, 2015; Lupton et al, 2016). These groups seem to have grown in popularity as information resources due to the diverse (and often similar) and relatable experiences available within them (Ellison and Vitak, 2015; Smock et al, 2011).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while not featured in the analysed media, the two hashtags featured here are not necessarily mutually exclusive. An ultrasound may end up being the sole image of record of an unborn child, and could potentially be used as part of a grieving process as well as a more celebratory announcement (for more discussion of social media and parental grief, see af Segerstad & Kasperowski, 2015).…”
Section: Method: Collecting Instagram Imagesmentioning
confidence: 99%
“…10 Research in palliative and bereavement care has shown that peer support in its various forms often serves as an important resource for coping. 11 In an Australian study, YAs with cancer reported that the opportunity to belong to a peer support group was one of the largest unmet needs during treatment. The same study also showed that peer support groups are valuable for managing emotional stress, and that peer support should be offered to all who need it.…”
Section: Introductionmentioning
confidence: 99%